Tau data-based evaluations of the hadronic vacuum polarization contribution to the muon g-2 - Pere Masjuan, Alejandro Miranda, Pablo Roig (SciPost Physics Proceedings)
We review the $τ$ data-driven computation of Euclidean windows for the hadronic vacuum polarization contribution to the muon anomalous magnetic moment ($a_μ$), which agree with the lattice results, making the difference of the $e^+e^-$ data-driven methods with them more intriguing. This conundrum needs to be solved by next year, when the final FNAL $a_μ$ measurement will be published, in order to extract firm conclusions on possible new physics effects.